Applying Nativist Theory in Arabic Language Acquisition: Insights from the “Ismu Fil Arabia” Activity in Elementary Schools - Syuhadak; M. Abdul Hamid; Mohammad Samsul Ulum; Mamluatul Hasanah; R. Taufiqurrochman (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: The study aims to explore Nativist theory application in Indonesian school environment. Nativism has been a pessimistic topic when discussing its implementation in the context of children’s education. This happens because the flow of its universal ability, which has been carried since birth, is not influenced by external elements like an Arabic language environment gifted by a teacher’s values. In fact, the understanding of Nativism is not that shallow; there are several indicators that are missed when looking at implicit phenomena in the role of Arabic language acquisition without involving this understanding.Methodology: Using a phenomenological approach related to the